Enterococcus species identified by MALDI-TOF MS in milk from dairy cow mastitis cases and herd surveys - Fernando Ulloa; Martina Penati; Valentina Monistero; Valerio Bronzo; Paolo Moroni; Miguel Salgado; Maria Filippa Addis (Veterinary Research Communications, 2025)
Enterococcus species are increasingly recognized as mastitis pathogens in dairy cows. Reliable species information is required for correctly defining the regional epidemiology of enterococcal mastitis, establishing its relationships with management variables, and understanding its impact on udder health. We investigated the species distribution of enterococci in bovine milk from subclinical mastitis (SCM) and clinical mastitis (CM) cases and full herd surveys (HS) using MALDI-TOF MS as identification method. A total of 21,864 milk samples from 106 dairy herds were routinely collected and analyzed according to the National Mastitis Council (NMC) guidelines over one year. Enterococcus spp. were found in 4.86% of CM, 5.05% of SCM, and 1.37% of HS milk samples. Overall, E. saccharolyticus was the most prevalent species (55.65%), followed by E. faecium (27.25%), and E. cecorum (5.51%), which showed a significant association with SCM (p-value = 0.0128). This study provides novel data on the Enterococcus species distribution in full herds survey and mastitis cases, highlighting the relevance of MALDI-TOF MS in refining enterococcal mastitis epidemiology, as true prevalence and species distribution may have been skewed by conventional biochemical tests.

Fecal carriage of extended-spectrum beta-lactamase (ESBL)-producing Escherichia coli in South American camelids and biosecurity practices among farms in northern Italy - Laura Filippone Pavesi; Maria Cristina Rapi; Martina Penati; Laura Musa; Federica Santandrea; Vincenzo Ferrulli; Ilaria Martucci; Antonio Boccardo; Guido Grilli; Maria Filippa Addis; Valerio Bronzo (Veterinary Research Communications, 2025)
South American camelids (SACs), particularly llamas ( Lama glama ) and alpacas ( Vicugna pacos ) are gaining popularity in Europe. Initially valued for their fiber and land management capabilities, these animals are now also kept for animal therapy, outdoor activities, and as companion animals. Despite their close interactions with humans and other animals, there is limited research on the transmission of microbes or antimicrobial resistance genes from SACs. This study aimed to survey the fecal carriage of extended-spectrum beta-lactamase ESBL-producing Escherichia coli (ESBL - E. coli) in SACs. A questionnaire was administered on-site to the farmers to survey management and biosecurity measures. Twelve farms from northern Italy (Lombardy, Piedmont, Veneto, and Emilia-Romagna) participated in the study. Fecal samples were analyzed to identify ESBL- E. coli and subjected to bacteriological culture on CHROMagar™ ESBL plates. Isolate identification was accomplished by MALDI-TOF MS, then subjected to the double-disk synergy test (DDST) and examined for 3 ESBL-encoding genes ( bla CTX−M , bla TEM , bla SHV ) via PCR analysis. A total of 125 SACs (19 llamas and 106 alpacas) were included. Four (3.2%) of these animals were positive for ESBL- E. coli . Two isolates carried the bla CTX−M gene; one had both bla CTX−M and bla TEM , and one was negative for all ESBL-encoding genes. Furthermore, none of the ESBL- E. coli isolates tested positive for the bla SHV gene. Several data from our questionnaire revealed a lack of biosecurity protocols, which aligns with other studies. The prevalence of ESBL-producing bacteria identified in this study was lower than in different other studies. Despite the low biosecurity levels observed on the SAC farms, our findings showed a low occurrence of ESBL- E. coli and a low carriage rate of multidrug-resistant (MDR) ESBL- E. coli .

Staphylococcus aureus and methicillin-resistant staphylococci and mammaliicocci in the bulk tank milk of dairy cows from a livestock-dense area in northern Italy - Sara Fusar Poli; Clara Locatelli; Valentina Monistero; Gustavo Freu; Paola Cremonesi; Bianca Castiglioni; Cristina Lecchi; Carla Maria Longheu; Sebastiana Tola; Alessandro Guaraglia; Carolina Allievi; Luca Villa; et al. (Research in Veterinary Science, 2025)

An update on non-aureus staphylococci and mammaliicocci in cow milk: unveiling the presence of Staphylococcus borealis and Staphylococcus rostri by MALDI-TOF MS - Martina Penati; Fernando Ulloa; Clara Locatelli; Valentina Monistero; Laura Filippone Pavesi; Federica Santandrea; Renata Piccinini; Paolo Moroni; Valerio Bronzo; Maria Filippa Addis (Veterinary Research Communications, 2024)
Non-aureus staphylococci and mammaliicocci (NASM) are the microorganisms most frequently isolated from milk. Given their numerosity and complexity, MALDI-TOF MS is one of the preferred species identification approaches. Nevertheless, reference mass spectra for the novel species Staphylococcus borealis were included only recently in the Bruker Biotyper System (MBT) library, and other species of veterinary interest such as S. rostri are still absent. This work provides an updated picture of the NASM species found in milk, gained by retrospectively analyzing the data relating to 21,864 milk samples, of which 6,278 from clinical mastitis (CM), 4,039 from subclinical mastitis (SCM), and 11,547 from herd survey (HS), with a spectrum library including both species. As a result, S. borealis was the second most frequently isolated NASM (17.07%) after S. chromogenes (39.38%) in all sample types, with a slightly higher percentage in CM (21.84%), followed by SCM (17.65%), and HS (14.38%). S. rostri was also present in all sample types (3.34%), reaching 8.43% of all NASM in SCM and showing a significant association ( p < 0.01) with this condition. Based on our findings, the presence of S. borealis and S. rostri in milk and their potential association with mastitis might have been overlooked, possibly due to the difficulties in differentiating these species from other closely related NASM. Our results indicate that S. borealis could be a more frequent contributor to bovine udder infections than previously thought and that S. rostri should also not be underestimated considering its significant association with SCM.

Non-aureus staphylococci and mammaliicocci isolated from bovine milk in Italian dairy farms: a retrospective investigation - Maria Filippa Addis; Clara Locatelli; Martina Penati; Sara Fusar Poli; Valentina Monistero; Lucia Zingale; Nicola Rota; Claudia Gusmara; Renata Piccinini; Paolo Moroni; Valerio Bronzo (Veterinary Research Communications, 2024)
Non- aureus staphylococci and mammaliicocci (NASM) are associated with bovine mastitis and increased milk somatic cell count (SCC) but their relationships with mammary gland health at the species level are not clearly defined. Regional differences have also been reported in their specific prevalence. The implementation of MALDI-TOF MS in milk microbiology is generating large and dependable datasets with the potential of providing useful epidemiological information. We present the retrospective analysis of 17,213 milk samples sent to our laboratory in 2021–2022, including 13,146 quarter samples from cows with subclinical (SCM) or clinical mastitis (CM) from 104 farms, and 4,067 composite herd survey (HS) samples from 21 farms. NASM were isolated from 21.12% of SCM, 11.49% of CM, and 15.59% of HS milk samples. The three most frequently identified NASM in SCM milk were Staphylococcus chromogenes (33.33%), S. haemolyticus (26.07%), and S. epidermidis (10.65%); together with S. microti and S. hyicus , these species were significantly more prevalent in quarters with SCM (p < 0.05). The three most frequently identified NASM in CM milk were S. chromogenes (31.69%), S. haemolyticus (21.42%), and Mammaliicoccus sciuri (18.38%), although no significant associations were found between these NASM species and CM. The three most frequently identified NASM in HS milk were S. chromogenes (44.49%), S. epidermidis (17.84%), and S. haemolyticus (17.23%), with S. chromogenes being isolated in all the farms sending HS milk (100%). In conclusion, this retrospective study provides the first information on the NASM species isolated from cow milk in Italy, expanding our knowledge on the epidemiology of NASM at the species level and providing further insights into their relationships with mammary gland health in modern dairy farms.

Production of recombinant proteins including the B-cell epitopes of autolysin A of Staphylococcus aureus isolated from clinical sheep mastitis and their potential for vaccine development - Elisa Azara; Antonio Carlo Foddai; Carla Maria Longheu; Maria Filippa Addis; Sebastiana Tola (Veterinary Research Communications, 2023)
Staphylococcus aureus is the most common clinical mastitis-associated pathogen in sheep which contributes to reduced welfare of affected animals and, therefore, compromises the quality and quantity of milk production. To prevent mastitis and its spread, it is essential to guarantee adequate breeding conditions and animal health, through the adoption of good farm management practices and the application of suitable biosecurity measures. Vaccination can play a strategic role in prevention, control, and eradication of diseases. The identification of secreted and cellular antigens of the predominant sheep-CC130/ST700/t1773 lineage would assist in the design of effective vaccine against mammary infections caused by S. aureus. In the current study, we carried out a 3D structural prediction analysis with the identification of the best B cell epitopes of the whole and secreted portion of S. aureus AtlA. Fragments of atl A, containing the main predicted epitopes, were amplified, cloned, and expressed in Escherichia coli for recombinant protein production. Two selected clones produced recombinant proteins (rAtl4 and rAtl8) showing strong reactivity with a hyperimmune serum against the native AtlA and with blood sera collected from sheep with clinical S. aureus mastitis. These may represent potential candidate protein-based vaccines able to elicit a protective immune response to be evaluated by vaccination and subsequent challenge of the vaccinated sheep.

Milk proteins as mastitis markers in dairy ruminants - a systematic review - Anna Giagu; Martina Penati; Sara Traini; Simone Dore; Maria Filippa Addis (Veterinary Research Communications, 2022)
Mastitis is one of the most impacting diseases in dairy farming, and its sensitive and specific detection is therefore of the greatest importance. The clinical evaluation of udder and mammary secretions is typically combined with the milk Somatic Cell Count (SCC) and often accompanied by its bacteriological culture to identify the causative microorganism. In a constant search for improvement, several non-enzymatic milk proteins, including milk amyloid A (M-SAA), haptoglobin (HP), cathelicidin (CATH), and lactoferrin (LF), have been investigated as alternative biomarkers of mastitis for their relationship with mammary gland inflammation, and immunoassay techniques have been developed for detection with varying degrees of success. To provide a general overview of their implementation in the different dairy species, we carried out a systematic review of the scientific literature using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analysis) guidelines. Our review question falls within the type “Diagnostic test accuracy questions” and aims at answering the diagnostic question: “ Which are the diagnostic performances of mastitis protein biomarkers investigated by immunoassays in ruminant milk?” . Based on 13 keywords combined into 42 searches, 523 manuscripts were extracted from three scientific databases. Of these, 33 passed the duplicate removal, title, abstract, and full-text screening for conformity to the review question and document type: 78.8% investigated cows, 12.1% sheep, 9.1% goats, and 6.1% buffaloes (some included more than one dairy species). The most frequently mentioned protein was M-SAA (48.5%), followed by HP (27.3%), CATH (24.2%) and LF (21.2%). However, the large amount of heterogeneity among studies in terms of animal selection criteria (45.5%), index test (87.9%), and standard reference test (27.3%) resulted in a collection of data not amenable to meta-analysis, a common finding illustrating how important it is for case definitions and other criteria to be standardized between studies. Therefore, results are presented according to the SWiM (Synthesis Without Meta-analysis) guidelines. We summarize the main findings reported in the 33 selected articles for the different markers and report their results in form of comparative tables including sample selection criteria, marker values, and diagnostic performances, where available. Finally, we report the study limitations and bias assessment findings.

Comparative evaluation of multiple protein extraction procedures from three species of the genus Caulerpa - Sarah Caronni; Filippa Addis; Maria Anna Delaria; Rodolfo Gentili; Chiara Montagnani; Augusto Navone; Pieraugusto Panzalis; Sandra Citterio (Journal of Applied Phycology, 2021)
The aim of this study was to define the simplest and least expensive protocol for total protein extraction for three different macroalgae of the genus Caulerpa (the invasive C. taxifolia and C. cylindracea and the autochthonous C. prolifera ). Five multi-step protein extraction procedures, set up for other macroalgal species, were tested. For each of them, different pre-treatment and extraction conditions were simultaneously examined, according to a factorial design, considering the starting material, the solvent-to-biomass ratio, and the incubation temperature. Protein yield in the obtained extracts was estimated with the Bradford method. Further, polyacrylamide gel electrophoresis (SDS-PAGE) was used to resolve proteins, assessing their quality and integrity. Significant differences in protein yield were observed among the extraction protocols and the conditions tested, also in relation to the considered species. Profiles having an acceptable quality were obtained for C. prolifera and C. cylindracea , and from the obtained results, the best method to obtain high yield and quality protein extracts for the two above-mentioned species appears to require the use of a primary TCA/acetone extraction buffer followed by a lysis buffer with NaCl, KCl, urea, Triton, SDS and a protease inhibitor. The best results, in particular, were obtained starting from fresh pulped material with a buffer-to-biomass ratio of 10:1 and an incubation temperature of 4°C. For C. taxifolia , instead, none of the tested protocols produced satisfactory results and further studies will be required.

Proteomic profiling of sea bass muscle by two-dimensional gel electrophoresis and tandem mass spectrometry - Genciana Terova; Salvatore Pisanu; Tonina Roggio; Elena Preziosa; Marco Saroglia; Maria Filippa Addis (Fish Physiology and Biochemistry, 2014)

Mycoplasma hominis and Trichomonas vaginalis symbiosis: multiplicity of infection and transmissibility of M. hominis to human cells - Paola Rappelli; Franco Carta; Giuseppe Delogu; Maria Filippa Addis; Daniele Dessì; Piero Cappuccinelli; Pier Luigi Fiori (Archives of Microbiology, 2001)